Compliance to patching in the treatment of amblyopia - Al-Yahya, Ahmed (Elsevier, 2012)
PURPOSE: To evaluate compliance of amblyopic patients to patching, and to identify reasons of poor compliance and suggest methods to overcome the problem. METHODS: We conducted a cross-sectional, retrospective study that included 37 families with a child diagnosed with unilateral amblyopia (age range 3–16 years) and attending the Pediatrics Ophthalmology clinic at the King Abdulaziz University Hospital (a tertiary eye hospital). Data were collected through interviews and from hospital charts. In the interviews we asked questions that sought information with regard to four aspects (domains); knowledge, attitude, insight and community’s effect. A score representing each domain was given to every family then we correlated these scores with family’s compliance percentage. RESULTS: When correlated with compliance, the insight and attitude domains showed a statistically significant correlation; p-value 0.002 and 0.004, respectively. However, the knowledge and community’s effect domains were not; p-value 0.084 and 0.114, respectively. Other qualitative factors affecting compliance were identified with open questions. Quotes from families of what they think can improve compliance are shown. CONCLUSION: To improve compliance, merely educating patients is not sufficient and more efforts should be undertaken toward ensuring true sense of the problem and its impact. Factors affecting compliance due to the physical properties in the patch itself should be addressed too (heat, irritation, poor adhesive material and design).